Evolusi Teknologi Jaringan Seluler Dari 4G Ke 5G : Sebuah Kajian Literatur Berbasis Arsitektur Dan Kinerja - Shintia Destrianita; Firdaus Nursal; Yulindon Yulindon (Kampus Akademik Publiser, 2026)
The development of wireless communication technology has entered the 5G era, designed to address global data traffic surges and low latency requirements through a shift in infrastructure paradigms. While previous studies have partially examined technical parameters, there remains a gap in comprehensive synthesis directly linking core architecture transformation to multi-parameter performance. This study aims to integrate the correlation between network architecture evolution, from Evolved Packet Core (EPC) to Service-Based Architecture (SBA), with empirical performance analysis including latency, throughput, and connection density using a Systematic Literature Review (SLR) of global research data from the last five years across IEEE Xplore, ScienceDirect, and MDPI databases. Analysis results indicate that the transition to SBA and the implementation of Multi-access Edge Computing (MEC) are key factors in drastically reducing latency compared to 4G. Empirically, 5G NSA networks can deliver throughput up to 180 Mbps, significantly surpassing 4G’s 10-12 Mbps, although signal stability at high frequencies remains a challenge in high-mobility conditions. This study concludes that the transformation toward service-based architecture and edge computing is the primary driver enabling significant performance leaps in 5G technology.